Air Waves Induced by Truck Passage in a Slender Motorway - Fabio Rizzo; Aleksander Pistol; Alberto Viskovic; Marco Petrangeli (Shock and Vibration)
The interaction between a pedestrian bridge for a motorway crossing and air pressure waves induced by the truck passage is discussed with reference to a slender footbridge in Pregnana (Italy). The experimental campaign was necessary, as very significant vibrations induced by truck passage were observed during the construction process before building the reinforced concrete plate on the deck. Results obtained from monitoring the air pressures and accelerations caused by the truck passage under the bridge along with truck speeds have shown a phenomenon known as a piston effect occurring during the passage. Based on the statistical analysis of these measured values, the spatial distribution of the wave on the bridge was elaborated. Numerical analyses of the bridge without the reinforced concrete plate on the deck suggest that the piston effect should be calculated to safely construct light bridges.